A STUDY ON OCCURRENCE OF ALGAE IN A STREAM HEAVILY POLLUTED WITH HOUSEHOLD WASTEWATER - Sonmez, Feray; Kocer, Mehmet Ali Turan; Alp, Mehmet Tahir; Sen, Bulent (Parlar Scientific Publications (P S P), 2018)
Aim of this study was to determine the algae occurring in organically polluted Haringet Stream which has been subjected to continous discharge of pre-treated waste water of Elazig Province. For this purpose the occurrence of algae at discharge part of sewage and in the unpolluted upper part of the stream was studied for a period of a year. Polluted part of the stream was richer in species composition whilst number of algal species was less in the clean upper part of the stream. The most of the algae recorded at discharge zone of sewage were diatoms, followed by blue-greens. In contrast, Chlorophyta and Euglenophyta were represented with less number of species and cell numbers. Diatom flora in polluted part of stream composed mainly of Fragilaria, Gomphonema, Navicula and Nitzschia spp. Oscillatoria spp. were the most noticable members of blue-green whilst Scenedesmus and Chlamydomonas spp. were conspicuous green algae in the polluted part. At species level, Brachysira micro-cephala, Gomphonema olivaceum, Navicula radiosa, Nitzschia dissipata, N minuta, N palea, N recta, Oscillatoria limosa, O. sancta, O. tenuis, Planktothrix rubescens, Pseudostaurosira brevistriata and Rhoicosphenia abbreviata were particularly noticable pollution algae with their high cell numbers and frequency of occurrence. The algae occurred in unpolluted part were only diatoms, mostly different species than those recorded in polluted part. Occurrence of algal species in polluted and unpolluted parts of the stream were discussed and evaluated in relation to pollution sensitivity and pollution tolerance. The normality of data was tested for each parameter using the Shapiro-Wilk test. Normally distributed season data were compared using a one-way analysis of variance (ANOVA), whereas those non-normally distributed data on water quality parameters were compared using either the Mann-Whitney (M-V) test for two groups.
Keywords: Algae; organic pollution; pollution sensitivity; Haringet Stream; Elazig; Turkey